Phytol supplementation alters plasma concentrations of formate, amino acids, and lipid metabolites in sheep - L.L. Ding; M. Matsumura; T. Obitsu; T. Sugino (Animal, 2021)
The phytol moiety in chlorophyll molecules acts as an agonist of peroxisome proliferator-activated receptor-α in monogastric animals. The current study aimed to clarify the effects of dietary supplementation with phytol on the plasma concentrations of formate and amino acids related to one-carbon (1C) donors and its effects on lipid metabolism in sheep. Four mature sheep were fed with a mixed ration (metabolizable energy, 10.7 MJ/kg DM; CP, 150 g/kg DM) comprising barley, rice bran, soybean meal, and oat hay at 1.5 times maintenance metabolizable energy for three consecutive 14-day experimental periods. The first and third periods served as controls without phytol supplementation, while in the second period, phytol was added to the mixed ration at 12 g/kg of dietary DM per day. In each period, feces, urine, and jugular blood samples were collected. Dry matter intake in relation to metabolic BW was slightly lower (P < 0.01) in the first period than the second and third periods but did not differ between the latter two periods. Dry matter digestibility was slightly reduced (P = 0.05) by the phytol treatment. Nitrogen (N) intake and retention showed similar trends to DM intake, but urinary N was unchanged among the periods. Plasma cholesterol and phospholipid concentrations decreased during the phytol treatment period, while triglyceride concentration increased (P < 0.05). In the phytol treatment period, the plasma concentrations of serine and glycine (1C donors) increased, but the glutamate level decreased (P < 0.01). Plasma concentrations of formate and methionine increased (P < 0.01) from the first control period to the phytol supplementation period, but homocysteine and cysteine (intermediate and by-product of the methionine cycle) levels were unchanged among the treatment periods. In conclusion, dietary phytol affects lipid metabolism as well as amino acid metabolism and 1C donors in sheep. These effects may be associated with the activity of phytol as an agonist of the nuclear receptors, although this needs further investigation.